Acute functional reorganisation of the human motor cortex during resection of central lesions: a study using intraoperative brain mapping. Issue 4 (1st April 2001) - Duffau, H
Abstract : OBJECTIVES: Brain plasticity is supposed to allow the compensation of motor function in cases of rolandic lesion. The aim was to analyse the mechanisms of functional reorganisation during surgery in the central area. METHODS: A motor brain mapping was performed in three right handed patients without any neurological deficit, operated on for a slow growing lesion near the rolandic region (two precentral resected under general anaesthesia and one retrocentral removed under local anaesthesia to allow also sensory mapping) using intraoperative direct electrical stimulations (5 mm space tips bipolar stimulator probe, biphasic square wave pulse current: 1 ms/phase, 60 Hz, 4 to 18 mA). RESULTS: For each patient, the motor areas of the hand and forearm in the primary motor cortex (M1) were identified before and after lesion removal with the same stimulation parameters: the same eloquent sites were found, plus the appearance after resection of additional sites in M1 inducing the same movement during stimulations as the previous areas. CONCLUSIONS: Multiple cortical representations for hand and forearm movements in M1 seem to exist. In addition, the results demonstrate the short term capacity of the brain to make changes in local motor maps, by sudden unmasking after tumour resection of a second redundant site participating in the same movement. Finally, it seems not necessary for the whole of the redundant sites to be functional to provide normal movement, a concept with potential implications for surgery within the central region.